A Nation Dedicated to Religious Liberty: The Constitutional Heritage of the Religion Clauses - Adams, Arlin M. (University of Pennsylvania Press, 2015)
Here is a concise overview of the historical development and judicial interpretation of the First Amendment religion clauses. It begins with a survey of the history of American religious liberty, goes on to present the views of the Founding Fathers, and then considers the core value of religious liberty and the constitutional purposes that implement that value.the book ends on a practical note by applying these principles to questions of equal access, religious symbolism in public life, and the task of defining religion for constitutional purposes. As the authors note in their introduction, "the historical principles that animate the religion clauses are more than an abstract intellectual exercise. . . . They provide an essential context for guiding the resolution of modern religious liberty issues.